Static and Dynamic Histomorphometric Data in 9- to 11-Year-Old Ewes - Turner, A.S.; Villanueva, A.R. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The technique of trans-iliac biopsy and subsequent histomorphometrical examination in ewes is reported. Biopsies were obtained from 18 clinically normal ewes, aged 9 to 11 years which had been given tetracycline intramuscularly twice, 11 days apart, at a dose rate of 20 mg/kg. There were no complications associated with the administration of the tetracycline at this dose and at this site. The core of the biopsy consisted of cancellous bone between two cortices allowing complete histomorphometric analysis from undecalcified sections. Two clearly distinct and separate labels were visible under ultraviolet light with the labelling method used. Primary, surface, volume and dynamic data were measured or calculated and are reported. Certain static and dynamic histomorphometric variables from this study were compared to those of other workers who used aged (but slightly younger) ewes, and there were many similarities between the studies. A comparison was also made of absolute values of bone volume (BV/TV%), relative osteoid volume (OV/BV%) and mineral apposition rate (MAR, mcm/day) of this study, and those of men and pre- and postmenopausal women reported in recently published data, as well as parameters of 14 elderly normal women measured by one of us. It was concluded that iliac crest biopsy in the ewe is a safe effective method to quantitate skeletal changes and our data compares favorably with other workers in this species. Furthermore, the BV/TV%, OV/BV% and MAR; of ewes of this age resembled that of both men and postmenopausal women at least in their 6th or 7th decade of life. Therefore 9- to 11-year-old ewes may be a useful models for studies and therapeutic trials of both osteopenia and osteoporosis of the skeleton.The article describes the technique of trans-iliac biopsy and subsequent histomorpho-metrical examination in aged ewes.
Keywords: Histomorphometry; sheep; osteoporosis; aging; labels; biopsy; iliac crest